Quality evaluation of monoclonal antibodies suitable for immunomagnetic purification of native tau protein - Jankovičová, Barbora; Hromádková, Lenka; Kupčík, Rudolf; Kašparová, Jitka; Řípová, Daniela; Bílková, Zuzana (Univerzita Pardubice, 2014)
Tau protein plays a crucial role in the neuronal cytoskeleton stabilization. Under the pathological conditions it can be abnormally phosphorylated which leads to aggregation and formation of neurofibrillary tangles representing pathological hallmark of Alzheimer's disease (AD). For its association with neurodegenerative diseases tau protein is intensively studied in various diagnostic and therapeutic applications. Since there is no standard of tau protein involving essential post-translational modifications it is often necessary to purify it directly from cerebrospinal fluid (CSF) or blood of healthy or AD clinical signs exhibiting organism. Immunomagnetic purification based on the isolation of target protein using a specific antibody bound to magnetic carrier is the most effective tool for this purpose. High quality antibodies are the main prerequisite of successful purification, but many commercial antibodies does not comply with the challenging requirements for immunosorbent preparation. In this work, we compared 4 different anti-tau monoclonal antibodies currently available on the market (clones HT7, BT2, 8F10, 7E5). The evaluation criteria were set along the intended use for the preparation of specific magnetic immunosorbent subsequently applicable for native tau protein purification. We evaluated the characteristics declared by producers as specificity, purity and homogeneity. We also tested the binding affinity and IgG stability during the covalent immobilization to the surface of magnetic microparticles and during the immunoprecipitation of intact tau protein or tryptic tau fragments. Results are summarized and discussed here.
Keywords: tau protein; Alzheimer’s disease; immunomagnetic purification; monoclonal antibody